Penggunaan Model Project Based Learning Melalui Pendekatan Fenomenologi Terhadap Kemampuan Berpikir Kritis Pada Pembelajaran IPA Kelas VI di MI Riyadlatul Athfal Hulaan Menganti Gresik - Fara Difa Nur Aini; Rahmat Rudianto; Nurul Agustin (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
This study aims to determine the effect of implementing the Project Based Learning (PJBL) learning model on improving students' critical thinking skills in learning Natural Sciences (IPA) in class VI MI Riyadlatul Athfal Hulaan Menganti Gresik. The method used is Classroom Action Research (CAR) which is carried out in two cycles. Data were collected through observation, tests, interviews, and documentation, then analyzed qualitatively and quantitatively. The results showed that the implementation of PJBL was able to increase teacher activity from 77.5% in cycle I to 100% in cycle II. Student activity also increased from 77.08% to 93.75%. The average value of student learning outcomes increased from 75 in cycle I to 93 in cycle II, with the percentage of learning completion increasing from 64% to 89%. These findings indicate that PJBL is effective in improving students' learning outcomes and critical thinking skills. PJBL allows students to be actively involved in completing projects, thinking scientifically, and applying concepts in real contexts. Thus, this model is worthy of being used as an innovative learning strategy in learning science in elementary schools.